Student Health Self-Evaluation and Gender Differences at University of Zagreb - Gošnik, Jelka (Array, 2012)
The satisfactory health of a student is important for overall quality of life and achieving required academic goals during undergraduate study. The aim of this study is to examine health survey among freshmen (1st year students) during 2011-2012 academic year at University of Zagreb in Croatia. The survey was conducted on random sample of 745 students (568 female and 177 male). Survey was voluntary, non-anonymous and it contributes to improvement of the quality of Physical and Health Culture (which is a mandatory course for freshmen at University of Zagreb). During self-evaluation of health students used five-level Likert’s scale from 1 (none) to 5 (very high). The difference between male and female students determined by t- test show statistically significant difference (p<0.05) in the mean values for the following variable: low blood pressure, circulation, lack of energy, headaches and migraines. This results showing elevated level of various health problems among freshmen indicate importance of regular physical activity to adequately deal with increasingly demanding student life of new generations.